For Public Service Or Money : Understanding Geographical Imbalances In The Health Workforce - Barr, Abigail (The World Bank, 2005)
Geographical imbalances in the health workforce have been a consistent feature of nearly all health systems, especially in developing countries. The authors investigate the willingness to work in a rural area among final year nursing and medical students in Ethiopia. Analyzing data obtained from contingent valuation questions, they find that household consumption and the student ' s motivation to help the poor, which is their proxy for intrinsic motivation, are the main determinants of willingness to work in a rural area. The authors investigate who are willing to help the poor and find that women are significantly more likely to help than men. Other variables, including a rich set of psycho-social characteristics, are not significant. Finally, the authors carry out some simulations on how much it would cost to make the entire cohort of starting nurses and doctors choose to take up a rural post